2011
DOI: 10.5581/1516-8484.20110117
|View full text |Cite
|
Sign up to set email alerts
|

Karyotypic and fluorescent in situ hybridization study of the centromere of chromosome 7 in secondary myeloid neoplasms

Abstract: BackgroundSecondary myeloid neoplasms comprise a group of secondary diseases following exposure to myelotoxic agents or due to congenital diseases. The improvement of anticancer agents and immunosuppressive drugs seem to be associated with an increased incidence of secondary myeloid neoplasms. Karyotyping of bone marrow is essential for diagnosis and prognosis. Previous use of alkylating agents and radiation are associated with clonal abnormalities such as recurrent unbalanced -5/5q-, -7/7q- and complex karyot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…4 The finding of monosomy 7 in this patient is expected in secondary myeloid neoplasia, including following exposure to alkylating agents such as the busulfan. 23 Reports describe MDS in patients with SCD who experienced graft failure and autologous reconstitution post-HLA-haploidentical HSCT using nonmyeloablative conditioning regimens, typically with alkylating agents. One report showed that 2 of 23 patients with hemoglobinopathies (21 with SCD and 2 with thalassemia) who received 400 cGy total-body irradiation and/or posttransplant addition of alkylating agent cyclophosphamide developed high-grade MDS.…”
Section: Resultsmentioning
confidence: 99%
“…4 The finding of monosomy 7 in this patient is expected in secondary myeloid neoplasia, including following exposure to alkylating agents such as the busulfan. 23 Reports describe MDS in patients with SCD who experienced graft failure and autologous reconstitution post-HLA-haploidentical HSCT using nonmyeloablative conditioning regimens, typically with alkylating agents. One report showed that 2 of 23 patients with hemoglobinopathies (21 with SCD and 2 with thalassemia) who received 400 cGy total-body irradiation and/or posttransplant addition of alkylating agent cyclophosphamide developed high-grade MDS.…”
Section: Resultsmentioning
confidence: 99%
“…Five patients (11.9%) had undergone autologous HSCT. The patient characteristics are shown in Table 1 and further information about clinical data are available in a previous publication 22 . The median latency between the primary disease and s-MN was 85 months (range: 23–221 months).…”
Section: Resultsmentioning
confidence: 99%
“…The results of karyotype and fluorescence in situ hybridization (FISH) studies have already been published. 22 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations